Surface analysis in the semiconductor industry: Present use and future possibilities. (1st April 2020) - van der Heide, Paul A.W.; Spampinato, Valentina; Franquet, Alexis; Zborowski, Charlotte; Conard, Thierry; Ludwig, Jonathan; Paredis, Kristof; Vandervorst, Wilfried; Pirkl, Alexander; Niehuis, Ewald
Abstract : Secondary ion mass spectrometry (SIMS), X‐ray photoelectron spectroscopy (XPS), and atomic force microscopy (AFM) represent three surface analysis techniques heavily used in the complementary metal oxide semiconductor (CMOS) industry. The maturity of these techniques is demonstrated by (a) the diversity of lab‐based instruments used in research and development (R&D) as well as to support fab‐related issues and (b) the fact that highly automated platforms have now been or are being introduced into the fab for process control. Some recent developments of interest in the lab R&D space include the following: (a) the introduction of Orbitrap mass spectrometers into SIMS, (b) the introduction of higher energy monochromated photon sources into standalone lab‐based XPS, and (c) the introduction of commercialized vacuum–scanning probe microscopy (SPM) platforms. The possibilities this opens are demonstrated through (a) SIMS analysis of organics from photoresist materials, (b) XPS subsurface analysis, ie, beyond the sputter front during depth profiling, and (c) SPM analysis of 2D material properties sensitive to the ambient environment, to mention a few.